2016
DOI: 10.1007/s00113-015-0134-4
|View full text |Cite
|
Sign up to set email alerts
|

Arthroskopisch assistierte Frakturversorgung am oberen Sprunggelenk

Abstract: Acute ankle fractures are one of the most common fractures in adults with an incidence of 0.1-0.2 % per year. Operative treatment by open reduction and internal fixation (ORIF) is the standard method of treatment for unstable or dislocated fractures. The main goal of the operation is the anatomical realignment of the joint and restoration of ankle stability; nevertheless, anatomical reduction does not automatically lead to favorable clinical results. According to several studies the mid-term and in particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
1
0
0
4
Order By: Relevance
“…The 1‐year follow‐up showed that AORIF lead to good to excellent results in complex ankle fractures [8]. This is in line with previous articles published by Braunstein et al [6], Liu et al [36] and Lee et al [34] However, Fuchs et al [27] showed no significant functional outcome improvement in patients who underwent AORIF. Another point of discussion is what the surgeon should do when detecting a (osteo)chondral lesion pre‐ or intra‐operatively.…”
Section: Discussionsupporting
confidence: 72%
“…The 1‐year follow‐up showed that AORIF lead to good to excellent results in complex ankle fractures [8]. This is in line with previous articles published by Braunstein et al [6], Liu et al [36] and Lee et al [34] However, Fuchs et al [27] showed no significant functional outcome improvement in patients who underwent AORIF. Another point of discussion is what the surgeon should do when detecting a (osteo)chondral lesion pre‐ or intra‐operatively.…”
Section: Discussionsupporting
confidence: 72%
“…Im Erwachsenenalter gehören Sprunggelenkfrakturen zu den häufigsten Frakturen [8]. Eine Vielzahl an Studien hat hierbei gezeigt, dass bei bis zu 90% aller Frakturen konsekutive Knorpelverletzungen vorkommen.…”
Section: Frakturenunclassified
“…Einige nichtbeeinflussbare Risikofaktoren für ein schlechtes Ergebnis wurden bereits identifiziert (hoher Body-Mass-Index, fortgeschrittenes Patientenalter, Verletzung mehrerer Malleoli, Syndesmoseninstabilität) [4,5]. Einige Faktoren können aber durch den Operateur positiv beeinflusst werden, wie beispielsweise die Qualität der Reposition, die Identifizierung und Behandlung von intraartikulären Begleitverletzungen, die anatomische und dauerhafte Wiederherstellung des distalen Tibiofibulargelenks sowie die Verminderung von Komplikationen durch die Wahl der geeigneten Operationstechnik [4,6,7]. Lange Zeit wurden bei der Behandlung der Sprunggelenkfrakturen althergebrachte Behandlungsstrategien und Dogmen unkritisch übernommen.…”
Section: Frakturen Des Sprunggelenkesunclassified